Social Imaginaries of Peru: Simulation and Simulacrum in the Advertising of the Inca Kola Soft Drink Brand - Rojas Virijivich, Rodolfo (2023)
This essay addresses the issue of social imaginaries in Peru and their relationship with the advertising of the Inca Kola soft drink brand, focusing on the concepts of simulation and simulacrum. Social imaginaries are shared representations that influence the way people perceive their social reality, and are expressed through stories, legends, myths and images. On the other hand, simulation refers to the creation of copies without an original, images of things that do not exist, and simulacrum implies the disturbance and challenge of reality itself. The reflection seeks to establish a link between these concepts and analyze how Inca Kola’s advertising constructs social imaginaries based on simulations, instead of reality. This raises the problem of idealizing aspects of reality that cannot be fulfilled, since simulation originates in the utopia of equivalence. According to Baudrillard (1994/1998, Chapter 2), we live in a society where reality and representations are confused, and simulation is based on the belief that everything can be replaced by its image.